THE RELATIONSHIP BETWEEN WORKING PERIOD AND NURSES' COMPLIANCE WITH SOPS FOR MEDICAL AND NON-MEDICAL WASTE DISPOSAL AT PATI ISLAMIC HOSPITAL - Indri Wahyuni; Feri Catur Yuliani; Yeni Rusyani; Akbar Amin Abdullah (RADJA PUBLIKA, 2025)
Hospital waste disposal compliance includes the procedures implemented. Improper sorting negatively impacts environmental quality and must be controlled according to applicable SOPs. To determine the relationship between length of service and nurses' compliance with SOPs for medical and non-medical waste disposal at Pati Islamic Hospital in 2025. The researchers used a quantitative study with a cross-sectional approach. The population was nurses at Pati Islamic Hospital, and a sample of 52 nurses was obtained using purposive sampling. Data analysis used the Chi-Square test using SPSS. A total of 20 respondents (38.5%) had the longest working period with a working period of >10 years, while 5 respondents (9.6%) had a minimum working period with a working period of <1 year. A Good compliance attitude was obtained by 48 respondents (92.3%), and 4 respondents had a Fair compliance attitude. In conclusion, there is no relationship between the length of service period and nurses' compliance with the SOP for medical and non-medical waste disposal based on the Chi-Square calculation obtained a value of 0.250, greater than the significance value of 0.05. The conclusion is that length of service does not affect nurses' compliance with SOPs for disposing of medical and non-medical waste at Pati Islamic Hospital. The researchers recommend further research with a more diverse population of respondents and other variables related to hospital waste disposal to compare the results.